Measurements of the Angular Distributions of Muons from gamma Decays in p(p)over-bar Collisions at root s=1.96 TeV - Aaltonen, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
The angular distributions of muons from Υ(1S,2S,3S) →μ +μ - decays are measured using data from pp̄ collisions at √s=1.96TeV corresponding to an integrated luminosity of 6.7fb -1 and collected with the CDF II detector at the Fermilab Tevatron. This analysis is the first to report the full angular distributions as functions of transverse momentum p T for Υ mesons in both the Collins-Soper and s-channel helicity frames. This is also the first measurement of the spin alignment of Υ(3S) mesons. Within the kinematic range of Υ rapidity |y|<0.6 and p T up to 40GeV/c, the angular distributions are found to be nearly isotropic. © 2012 American Physical Society.